Induced abortion. Issue 6 (10th April 2017) - ,; Cameron, S.; Glasier, A.; Lohr, P.A.; Moreau, C.; Munk-Olssen, T.; Oppengaard, K.S.; Templeton, A.; Van Look, P.; Baird, D.T.; Crosignani, P.G.; La Vecchia, C.; et al.
Abstract: Abortion is common. Data on abortion rates are inexact but can be used to explore trends. Globally, the estimated rate in the period 2010–2014 was 35 abortions per 1000 women (aged 15–44 years), five points less than the rate of 40 for the period 1990–1994. Abortion laws vary around the world but are generally more restrictive in developing countries. Restrictive laws do not necessarily deter women from seeking abortion but often lead to unsafe practice with significant mortality and morbidity. While a legal framework for abortion is a prerequisite for availability, many laws, which are not evidence based, restrict availability and delay access. Abortion should be available in the interests of public health and any legal framework should be as permissive as possible in order to promote access. In the absence of legal access, harm reduction strategies are needed to reduce abortion-related mortality and morbidity. Abortion can be performed surgically (in the first trimester, by manual or electric vacuum aspiration) or with medication: both are safe and effective. Cervical priming facilitates surgery and reduces the risk of incomplete abortion. Diagnosis of incomplete abortion should be made on clinical grounds, not by ultrasound. Septic abortion is a common cause of maternal death almost always following unsafe abortion and thus largely preventable. While routine follow-up after abortion is unnecessary, all women should be offered a contraceptive method immediately after the abortion. This, together with improved education and other interventions, may succeed in reducing unintended pregnancy.